STUDY ON MESHING CHARACTERISTICS AND FATIGUE LIFE OF CYCLOIDAL SPUR GEARS WITH LOW SLIDING RATE - XU JianMin; ZHENG QingJie; LIU Kun; GONG XiaoYan; SONG Lei (Jixie qiangdu)
In order to improve the transmission performance of gears,a low sliding rate cycloidal spur gear based on the meshing line principle was presented.Firstly,the equations of gear sub tooth profile and transition curve were derived from the gear meshing principle.Then,the maximum degree of overlap was calculated as 3.0134 based on the gear meshing principle and the overlap equation.Finally,computer simulation was conducted to analyze the stability,contact stress and fatigue life during the meshing process.The results show that the tangential meshing force between the teeth of the high overlap cycloidal gear is 1238.2 N,which is 5.24%smaller than that of the involute standard gear under the same working condition.The fatigue life analysis shows that the minimum fatigue life is 4.534×106times,and the tooth surface contact stress is mainly concentrated in the gear meshing position and the tooth root part,so the fatigue damage is easy to occur in the driving gear and driven gear meshing and tooth root part.